Considerations regarding the Corporeal Contingence of the Soul - qasem sobhani; hadi yasaqi (حکمت اسرا)
The transcendental theosophists believe that human soul is spiritual in respect to survival and contingence. In contrast to this theory, Mulla Sadra believes that the soul is corporeal in respect to contingence and spiritual in respect to survival. The main reason why Mulla Sadra has turned to this theory is the criticisms that he has leveled at the theory of the spiritual contingence. This paper seeks to explain the concept of corporeal contingence of the soul using Mulla Sadra’s terms, and also demonstrate that Mulla Sadra’s remarks in this regard are not always the same. It will, the, explain Mulla Sadra’s critique of the spiritual contingence theory and will conclude its discussion by defending the stance of the Peripatetic school by answering the criticisms leveled at it by Mulla Sadra.